2019
DOI: 10.3906/sag-1811-198
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of malignancy with thyroid imaging reporting and data system (TI-RADS) in thyroid nodules with persistent nondiagnostic cytology

Abstract: Background/aim: We aimed to evaluate the utility of thyroid imaging reporting and data system (TI-RADS) in prediction of malignancy in thyroid nodules with persistent nondiagnostic (ND) cytology. Materials and methods:A total of 246 thyroid nodules which were surgically removed and had at least two fine-needle aspirations (FNAs) with ND cytology were included in this study. Ultrasonography features and TI-RADS scores were recorded.Results: Of 246 nodules, 218 (88.6%) had benign and 28 (11.4%) had malignant fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…In literature, many studies aiming to predict preoperative malignancy in patients with ND TNs are generally concentrated on Thyroid imaging reporting and data system (TI-RADS) [3,18]. In their study of 246 patients with persistent ND TNs, Başer et al could not reveal any suspicious ultrasonographic features for predicting malignancy or did not point out any difference between benign and malignant nodules in terms of TI-RADS scores [3]. However, Yoon et al concluded that the malignancy risk stratification with TIRADS for ND TNs is more effective than the Bethesda system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, many studies aiming to predict preoperative malignancy in patients with ND TNs are generally concentrated on Thyroid imaging reporting and data system (TI-RADS) [3,18]. In their study of 246 patients with persistent ND TNs, Başer et al could not reveal any suspicious ultrasonographic features for predicting malignancy or did not point out any difference between benign and malignant nodules in terms of TI-RADS scores [3]. However, Yoon et al concluded that the malignancy risk stratification with TIRADS for ND TNs is more effective than the Bethesda system.…”
Section: Discussionmentioning
confidence: 99%
“…The Bethesda I category includes inadequate cytological results reported as unsatisfactory or nondiagnostic (ND). The incidence of ND cytology is reported in the literature, ranging from 3% to 36.4% [3]. In cases with ND cytology, the estimated overall risk of malignancy is 5%-10%, while this rate is 9%-32% in surgically treated ones [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid imaging reporting and data system (TI-RADS) grading is recommended for ultrasound examination of thyroid nodules in several aspects, such as the boundary of thyroid nodules, internal echo, the existence of capsule, shape regularity, distribution of blood flow, aspect ratio, and microcalcifications, which is of definitive diagnostic value in distinguishing malignant thyroid tumors from benign ones. [ 5 ] Most of the thyroid malignant tumors are primary tumors, in which papillary thyroid carcinoma is the most common type. [ 6 ] Ultrasound images of papillary thyroid carcinoma mainly show single lesions with unclear boundaries, no capsule, irregular shape, the aspect ratio of larger than 1, hypoecho, and poor blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the subjectivity of ultrasound examination, the different experience of diagnostic physicians, and the overlapping of ultrasound signs of benign and malignant thyroid nodules, some nodules that should have been diagnosed as TI‐RADS grade 3 or 5 were classified as TI‐RADS 4. The identification of benign and malignant nodules is the focus and difficulty of ultrasound diagnosis 6 . Although surgical resection and pathological examination are the gold standard for differentiating benign and malignant thyroid nodules, noninvasive diagnostic methods are more easily accepted by patients and can avoid unnecessary biopsy and surgery.…”
mentioning
confidence: 99%